The Correlation between Game Watching Intensity, Youtube, Tiktok with Emotional Intelligence - Kusuma, Anggi; Nur, Sulistia; Aulia, Faridatul (GLOBAL HEALTH SCIENCE GROUP, 2025)
Indonesia has the highest prevalence of device use (69%), followed by Nigeria (81%), India (79%), and South Africa (78%), according to a global survey. The number of youngsters with emotional mental problems is rising in tandem with the facts. Emotional and mental health issues in children rose 4,0% between 2013 and 2018. Online games, TikTok, and YouTube are frequently utilized gadget applications. Objective: The research objective was to determine the correlation between the intensity of watching games, YouTube, and TikTok and emotional intelligence in elementary school children. Method: The type of research used in this study is quantitative. with the approach method used is cross sectional. The sample in this study were elementary school students who used the gadget applications youtube, tiktok and online games as many as 74 students. The sampling technique used Purposive Sampling. Bivariate analysis using the Gamma test. Results: The study's findings indicated that while emotional intelligence was primarily in the medium to low range, the intensity of viewing online games, YouTube, and TikTok was primarily in the high range. A positive correlation value with a p value <0,05 was obtained from the gamma test analysis, indicating a relationship between emotional intelligence and the amount of time spent viewing online games, YouTube, and TikTok. Conclusions: Controlling the intensity of children's gadget use is one way that parents or other caregivers can optimize positive effects and minimize negative ones.